Cueing musical emotions: An empirical analysis of 24-piece sets by Bach and Chopin documents parallels with emotional speech - Poon, Matthew; Schutz, Michael (Frontiers in Psychology, 2015)
Acoustic cues such as pitch height and timing are effective at communicating emotion in both music and speech. Numerous experiments altering musical passages have shown that higher and faster melodies generally sound “happier” than lower and slower melodies, findings consistent with corpus analyses of emotional speech. However, equivalent corpus analyses of complex time-varying cues in music are less common, due in part to the challenges of assembling an appropriate corpus. Here we describe a novel, score-based exploration of the use of pitch height and timing in a set of “balanced” major and minor key compositions. Our corpus contained all 24 Preludes and 24 Fugues from Bach’s Well Tempered Clavier (book 1), as well as all 24 of Chopin’s Preludes for piano. These three sets are balanced with respect to both modality (major/minor) and key chroma (“A”, “B”, “C”, etc.). Consistent with predictions derived from speech, we found major-key (nominally “happy”) pieces to be two semitones higher in pitch height and 29% faster than minor-key (nominally “sad”) pieces. This demonstrates that our balanced corpus of major and minor key pieces uses low-level acoustic cues for emotion in a manner consistent with speech. A series of post-hoc analyses illustrate interesting trade-offs, with